Faktor-faktor yang Mempengaruhi Kinerja Organisasi Perangkat Daerah (OPD) Kota Pekanbaru - Agustiawan, Agustiawan; Balqis, Faradila; Putri, Adriyanti Agustina (Akuntansi & Ekonomika, 2023)
This study aims to examine the influence of oversight, accountability, financial transparency and internal controlsystems on the performance of the Pekanbaru City Regional Apparatus Organization (OPD). Method used for data collection was a questionnaire. The population in this study were employees at 33 OPD in Pekanbaru City. Sampling using purposive sampling method, with a total sample of 145 respondents. This research is a quantitative study with the data obtained processed using IBM Statistics SPSS 25. The results of the study indicate that supervision, accountability, financial transparency and internal control systems partially affect the performance of the Pekanbaru City Regional Organization.